The specific endurance tennis test (SET-Test): design, reliability, and validity - Baiget, E.; Iglesias, X.; Vallejo, L.; Rodriguez, F. A. (Archivos de medicina del deporte, 2008)
A new procedure to assess tennis specific endurance was evaluated as to its application for testing and research purposes. Materials and methods: 38 trained male tennis players performed a maximal, incremental field test (SET-Test) conducted by a tennis ball throwing machine. 12 players performed the test three times, one with a portable gas analyzer. Results: Test duration was 13:39 ± 01:34 min:s (6.61 ± 0.82 stages); VO2max was 57.0 ± 6.0 mL•kg•min -1 ; technical effectiveness (TE) was 63.1 ± 9.1 % of successful shots. A TE deflection point (TEDP) was observed at stage 5.2 ± 1.1 (79.6 ± 14.6 % of final stage). A heart rate deflection point (HRDP) was observed in 92% of the subjects at an average of 178.6 ± 8.7 beats•min -1 (92.2 ± 2.7 % of HR max ); HRDP significantly correlated with the second ventilatory threshold (VT2) (r = 0.87, p<0.001). Low to moderate significant correlations (0.35 < r <0.55, p<0.05) were found between test results and the competitive level of the players. TE together with VT2 and VO2max, respectively, explained 56% and 53% of competitive level. Physiological and load measurements showed good consistency (intraclass correlation coefficients for HR max : 0.91, coefficient of variation = 1.4%; HRDP: 0.87, 2.5%; final stage: 0.85, 2.0%), somewhat higher than TE parameters (TE: 0.72, 4.7%; TEDP: 0.59, 6.1%). No differences in performance were found when using the portable gas analyzer. Conclusions: The SET-Test is an objective, valid, and reliable field test for the assessment of load, physiological, and technical efficiency parameters, allowing estimations of the VT2 in tennis players. Performance predictive capacity is moderate according to the multifactorial character of the game (Figure 1)